Study on the association SLC17A1 rs1165196 with gout in Vietnamese population - Duong, Nguyen Thuy; Tinh, Nguyen Doan; Minh Thang, Nguyen Tran; Ha, Nguyen Hai; Hai, Nong Van (Vietnam Journal of Biotechnology, 2018)
Gout is a common form of inflammatory arthritis caused by urate crystals in a joint from high levels of serum uric acid (SUA). The development of gout is not only triggered by environmental factors but also by genetic variants of individuals. Previous studies demonstrated that the genetic association with gout risk varies in different ethnic populations. The aim of this study was to assess the relationship between SLC17A1 rs1165196 and gout. A total of 169 patients with gout and 351 age-matched healthy controls were recruited at the Nguyen Trai hospital in Southern Vietnam for genomic DNA extraction. Genotypes of SLC17A1 rs1165196 were obtained using PCR-RFLP. Chi-Square test ( <!--?mso-application progid="Word.Document"?--> 16Ï‡"> 2) was used to test whether allele distribution of rs1165196 follows Hardy-Weinberg Equilibrium (HWE). Associations of the clinical characteristics between gout patient and control groups were assessed using Mann-Whitney U. Chi-Square test or Fisher’s exact test was used to check four models (additive, recessive, dominant, co-dominant) for association of rs1165196 with gout. The results showed that SLC17A1 rs1165196 was in accordance with HWE (p>0.05) and the genotype frequencies of AA, AG and GG were 0.57, 0.38 and 0.05, respectively. The most differences between gout patient and control groups were uric acid and hyperuricemia (p=0.000). Other clinical characteristics such as BMI and CRP levels were also significantly different between gout patient and control groups (p<0.05). However, there was no association of SLC17A1 rs1165196 with the risk of gout in Vietnamese population (p>0.05). Further study with larger sample size should be implemented to confirm our results on the association of SLC17A1 rs1165196 and gout in the Vietnamese population.